2016
DOI: 10.1016/j.physrep.2016.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Explosive transitions in complex networks’ structure and dynamics: Percolation and synchronization

Abstract: Percolation and synchronization are two phase transitions that have been extensively studied since already long ago. A classic result is that, in the vast majority of cases, these transitions are of the second-order type, i.e. continuous and reversible. Recently, however, explosive phenomena have been reported in complex networks' structure and dynamics, which rather remind first-order (discontinuous and irreversible) transitions. Explosive percolation, which was discovered in 2009, corresponds to an abrupt ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
192
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(207 citation statements)
references
References 444 publications
(1,105 reference statements)
4
192
0
3
Order By: Relevance
“…Moreover, Boccaletti et al discovered that instead of classic result of the second-order type, i.e. continuous and reversible, in complex networks' structure and dynamics, the synchronizing process rather reminds first-order (discontinuous and irreversible) transitions [19]. For evolutionary games in multiplex network, interactions between layers influence evolution of cooperation [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Boccaletti et al discovered that instead of classic result of the second-order type, i.e. continuous and reversible, in complex networks' structure and dynamics, the synchronizing process rather reminds first-order (discontinuous and irreversible) transitions [19]. For evolutionary games in multiplex network, interactions between layers influence evolution of cooperation [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a novel synchronization process exhibiting hypersensitivity or explosiveness in the natural physical and biological systems, called explosive synchronization (ES), has drawn much attention in the scientific community [1][2][3][4][5][6][7][8]. The epileptic seizures in the brain [9], chronic pain in the Fibromyalgia brain [10], the cascading failure of power grids [11], and the jamming of the internet [12] have shown ES transitions with small initial perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a special phase coherence (called the Bellerophon state) has been characterized in globally coupled nonidentical phase oscillators. Such a state is a quantized, time-dependent, clustered state which emerges close to a first-order-like transition to synchronization [2][3][4][5]. There are two main backgrounds of this work: the first is explosive synchronization, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Zhang et al proposed a frequencyweighted Kuramoto model, which can exhibit first-order-like synchronization transition on generic networkʼs topologies for typical frequency distributions [8][9][10][11][12]. Furthermore, it was revealed that the mechanism at the basis of such abrupt synchronization transition is similar to that underlying explosive percolation [2], where the formation of a giant component is controlled by a suppressive rule [10]. Finally, first-order-like synchronization transition was also found in adaptive and multi-layer networks [11].…”
Section: Introductionmentioning
confidence: 99%